2016
DOI: 10.1016/j.msea.2015.10.077
|View full text |Cite
|
Sign up to set email alerts
|

A high temperature mechanical study on PH 13-8 Mo maraging steel

Abstract: a b s t r a c tHigh temperature mechanical measurements were conducted to study the effect of the dynamic precipitation process of PH 13-8 Mo maraging steel. Yield stress, ultimate tensile strength, total elongation, hardness, strain rate sensitivity and activation volume were evaluated as a function of the temperature. The dynamic changes in the mechanical properties at different temperatures were evaluated and a balance between precipitation hardening and annealed softening is discussed. A comparison between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Optical micrographs of A0, A4, A5.25 and A6 are shown in Figure 1, while similar microstructure investigations for PH 13-8 Mo were carried out in [18,19]. As it can be observed, the microstructure of the sample A0 has large and irregular massive martensite blocks.…”
Section: A Workpiece Materialsmentioning
confidence: 67%
“…Optical micrographs of A0, A4, A5.25 and A6 are shown in Figure 1, while similar microstructure investigations for PH 13-8 Mo were carried out in [18,19]. As it can be observed, the microstructure of the sample A0 has large and irregular massive martensite blocks.…”
Section: A Workpiece Materialsmentioning
confidence: 67%
“…The experimental steel could be considered to be characterized by a high-strength and high-toughness combination, and the heat treatment improved the mechanical properties significantly [27][28] . The ultimate tensile strength (1930 MPa) is much higher than those of the presently commercial high-performance MSS (~ 1000-1500 MPa) [3][4][5][6][7][8][9] . The steel has acceptable tensile ductility (34% reduction in area and 10% of elongation) and high fracture toughness (86 MPa m 1/2 ).…”
Section: Hardness and Tensile Propertiesmentioning
confidence: 84%
“…Since firstly developed in 1946 by Carnegie-Illionois Steel Corporation, maraging stainless steels (MSS) have been widely used for many applications, for example, aircraft landing gear parts, petrochemical applications, and nuclear reactor components, because these steels present excellent comprehensive performance including ultra-high strength, excellent fracture toughness, good weldability and adequate corrosion resistance [1][2][3][4][5][6][7][8][9] . The representatives, PH 17-4 [3][4] , PH 13-8 [5][6] and PH 15-5 [7][8][9] have become essential in aerospace and defense applications. However, to satisfy the high standard of the next generation aircraft which has higher speed and larger carrying capacity, materials with super high strength are of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations on PHSS have been carried out, and most of them focus on mechanical and corrosion behavior [ 12 , 16 , 28 , 29 , 30 , 31 , 32 ]. Tian et al [ 28 ] have developed a novel stainless steel with distinguished strength and toughness balance properties and acceptable anti-corrosion properties.…”
Section: Effects Of Chemical Composition and Its Fluctuation On Micro...mentioning
confidence: 99%
“…Ronald Schnitzer et al have demonstrated that the reverted austenite in PH13-8Mo steel aged at 575 °C shows two types forms, and the precipitation of B2-NiAl precipitates and the formation of reversed austenite occur simultaneously. Meanwhile, the enhancement of the strengthening capability of B2-NiAl precipitates is related to the growth of B2-NiAl precipitates and the formation of B2-NiAl precipitates alters the strain rate sensitivity [ 15 , 16 , 17 ]. Furthermore, it is necessary to further rapidly model the relationship among alloy composition, process/microstructure, and properties.…”
Section: Introductionmentioning
confidence: 99%